THE REGIONAL GOVERNMENT'S STRATEGY TO OVERCOME THE CIRCULATION OF ALCOHOLIC BEVERAGES IN KESU DISTRICT, NORTH TORAJA REGENCY - Fransiska Linda; Muh Nur Yamin; Herman Herman (Universitas Negeri Makassar, 2026)
This study aims to find out the Regional Government's Strategy to Overcome the Circulation of Alcoholic Beverages in Kesu District, North Toraja Regency. This research uses a qualitative approach and produces descriptive data. Data collection was used by observation techniques, interviews, documentation and questionnaire distribution. The Data Analysis technique uses SWOT Analysis and conclusion test drawn. The results of this study show that the Regional Government's Strategy in Countering the Circulation of Alcoholic Beverages in Kesu District, North Toraja Regency has several efforts, namely tightening licensing and carrying out supervision and enforcement against the circulation of alcoholic beverages. However, the government needs to increase the special budget for the supervision of alcoholic beverages so that supervision and counseling can run effectively. Using SWOT analysis, the results obtained from this study are at the point of Quadrant III supporting the Turn-Arround Strategy, namely how external opportunities (Opportunities) can be used to overcome weaknesses (Weaknesses).